2018
DOI: 10.1016/j.ydbio.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Tfap2e/AP-2ε plays a pivotal role in maintaining the identity of basal vomeronasal sensory neurons

Abstract: The identity of individual neuronal cell types is defined and maintained by the expression of specific combinations of transcriptional regulators that control cell type-specific genetic programs. The epithelium of the vomeronasal organ of mice contains two major types of vomeronasal sensory neurons (VSNs): 1) the apical VSNs which express vomeronasal 1 receptors (V1r) and the G-protein subunit Gαi2 and; 2) the basal VSNs which express vomeronasal 2 receptors (V2r) and the G-protein subunit Gαo. Both cell types… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 44 publications
10
62
0
Order By: Relevance
“…To test the effects of Smad4 conditional ablation in maturing basal VSNs, we analyzed the cell composition and maturation state of cells in the VNE at P15. At this stage, we found a small but significant increase in the number of proliferative (Ki67+) cells, which suggests a compensatory response to epithelial cell loss (Lin et al, 2018), ( Fig. 3 A,B,C).…”
Section: Ap-2εcre Driven Smad4 Ablation Shows No Clear Abnormalities mentioning
confidence: 67%
See 4 more Smart Citations
“…To test the effects of Smad4 conditional ablation in maturing basal VSNs, we analyzed the cell composition and maturation state of cells in the VNE at P15. At this stage, we found a small but significant increase in the number of proliferative (Ki67+) cells, which suggests a compensatory response to epithelial cell loss (Lin et al, 2018), ( Fig. 3 A,B,C).…”
Section: Ap-2εcre Driven Smad4 Ablation Shows No Clear Abnormalities mentioning
confidence: 67%
“…However, the reduction in cFos activation in the anterior AOB likely indicates a postsynaptic defect secondary to Smad4 ablation in the mitral cells of the aAOB. In fact, we previously reported that some of the mitral cells of the AOB are positive for AP-2ε lineage (Lin et al, 2018).…”
Section: Exposurementioning
confidence: 93%
See 3 more Smart Citations